Tuberculum Sellae Meningioma vs Macroadenoma Hypophysis : How to Differentiate Preoperatively? Tuberculum Sellae Meningioma vs Macroadenoma Hypophysis : How to Differentiate Preoperatively? - Mardjono, Ignatius; Arifin, Muhammad Z.; Sidabutar, Roland; Singh, Arwinder; Ompusunggu, Sevline E. (The ASEAN Journal of Radiology, 2025)
Background: Sellar region tumors may origin from a various number of structures and each of them have a specific clinical and radiological appearance. Among these pathological processes, one of the most challenging is to distinguish between tuberculumsellae meningioma and macroadenomahypophysis. Differentiating these two entities preoperatively is very important to decide which approach will be most suitable and beneficial. The purpose of this study is to produce a simple preoperative scoring system to differentiate these two that can be used in specific conditions where MRI is not avalable or could not be performed. Methods: This analytical retrospective cohort study contains data obtained from patients treated in Neurosurgery Department of Hasan Sadikin General Hospital-Bandung from 1 January 2008 until 31 December 2010. 34 patients were enrolled in this study, in which 15 of them were diagnosed with macroadenomahypophysis and remainining 19 patients as tuberculumsellae meningioma which was confirmed with pathology examination. Results: From clinical presentation we found that the event of endocrinopathyoccurs significantly in macroadenoma hypophysis (p=0.0.002). Whereas from radiological evaluation there were 7 parameters that significantly distinguish these two enties including hyperostosis, sellar floor configuration, homogeneity of mass, confrast agent enhancement, waist configuration, peritumoral edema, and duralattachment. From these findings, we propose a simple scoring system to differentiate macroadenomahypophysis and tuberculumsellae meningioma with a 84.2% sensititivity and 100% specificity. Conclusion: Although MRI is the modality of choice in differentiating macroadenoma hypophysis and tuberculum sellae meningioma but our scoring system can be used as an aid in choosing best surgicallical approach.